Chilhaka (Toothed Leaf Chilla): An Underexplored Plant - Vyas, Abhay; Yadav, Vipin Kumar; Mishra, Rajesh Chandra (International Research Journal of Ayurveda & Yoga, 2020)
There are many plants on our planet which need a lot of study yet and one such plant is Chilhaka (Toothed leaf Chilla ). The plant possess anti diabetic, anti- microbial and diuretic property. It is also used in diabetes, ring worm, ascites, ulcers, wound, snake bite, fever etc. Ethanolic extract showed anti inflammatory activity in rats. Chilhaka suppresses the vata and kapha doshas, nourishes the Dhatus (the7 dhatus described in classical Ayurveda texts), is Agneya, and its fruit has properties of Vish (Poison) and thus is fatal for fish.